PERLINDUNGAN HUKUM MASYARAKAT TERDAMPAK PENCEMARAN LINGKUNGAN OLEH INDUSTRI - ABIDIN, ZAINAL (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2020)
HakÃƒâ€šÃ‚Â  atasÃƒâ€šÃ‚Â  lingkunganÃƒâ€šÃ‚Â  hidupÃƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â  baikÃƒâ€šÃ‚Â  danÃƒâ€šÃ‚Â  sehatÃƒâ€šÃ‚Â  sebagaimanaÃƒâ€šÃ‚Â  diaturÃƒâ€šÃ‚Â  dalamÃƒâ€šÃ‚Â  PasalÃƒâ€šÃ‚Â  28 (h) Undang-UndangÃƒâ€šÃ‚Â  DasarÃƒâ€šÃ‚Â  NegaraÃƒâ€šÃ‚Â  RepublikÃƒâ€šÃ‚Â  Indonesia(UUDÃƒâ€šÃ‚Â  1945)Ãƒâ€šÃ‚Â  membawaÃƒâ€šÃ‚Â  implikasiÃƒâ€šÃ‚Â  hukumÃƒâ€šÃ‚Â  agarÃƒâ€šÃ‚Â  negaraÃƒâ€šÃ‚Â  selaluÃƒâ€šÃ‚Â  menyediakanÃƒâ€šÃ‚Â  kualitasÃƒâ€šÃ‚Â  lingkunganÃƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â  sesuaiÃƒâ€šÃ‚Â  denganÃƒâ€šÃ‚Â  normaÃƒâ€šÃ‚Â  dasar UUDÃƒâ€šÃ‚Â  1945Ãƒâ€šÃ‚Â  tersebut.Ãƒâ€šÃ‚Â  BahkanÃƒâ€šÃ‚Â  dalamÃƒâ€šÃ‚Â  PasalÃƒâ€šÃ‚Â  33Ãƒâ€šÃ‚Â  UUDÃƒâ€šÃ‚Â  1945Ãƒâ€šÃ‚Â  telahÃƒâ€šÃ‚Â  diamanatkanÃƒâ€šÃ‚Â  bahwaÃƒâ€šÃ‚Â  ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œBumi, air, danÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  kekayaanÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  alamÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  terkandungÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  diÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  dalamnyaÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  dikuasaiÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  olehÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  negaraÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  danÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  dipergunakan Ãƒâ€šÃ‚Â Ãƒâ€šÃ‚Â untukÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  sebesar-besarÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  kemakmuranÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  rakyatÃƒÂ¢Ã¢â€šÂ¬Ã‚Â. GunaÃƒâ€šÃ‚Â  mewujudkanÃƒâ€šÃ‚Â  perlindunganÃƒâ€šÃ‚Â  terhadapÃƒâ€šÃ‚Â  lingkungan,Ãƒâ€šÃ‚Â  makaÃƒâ€šÃ‚Â  pemerintahÃƒâ€šÃ‚Â  mengeluarkanÃƒâ€šÃ‚Â  berbagaiÃƒâ€šÃ‚Â  kebijakanÃƒâ€šÃ‚Â  hukumÃƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â  terkaitÃƒâ€šÃ‚Â  denganÃƒâ€šÃ‚Â  masalahÃƒâ€šÃ‚Â  lingkunganÃƒâ€šÃ‚Â  hidupÃƒâ€šÃ‚Â  danÃƒâ€šÃ‚Â  salahÃƒâ€šÃ‚Â  satuÃƒâ€šÃ‚Â  produkÃƒâ€šÃ‚Â  hukumÃƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â  sangatÃƒâ€šÃ‚Â  pentingÃƒâ€šÃ‚Â  adalahÃƒâ€šÃ‚Â  Undang-undang NomorÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  32Ãƒâ€šÃ‚Â  TahunÃƒâ€šÃ‚Â  2009Ãƒâ€šÃ‚Â  tentangÃƒâ€šÃ‚Â  PerlindunganÃƒâ€šÃ‚Â  danÃƒâ€šÃ‚Â  PengelolaanÃƒâ€šÃ‚Â  LingkunganÃƒâ€šÃ‚Â  Hidup. UUPPLHÃƒâ€šÃ‚Â  telahÃƒâ€šÃ‚Â  memberikanÃƒâ€šÃ‚Â  dasarÃƒâ€šÃ‚Â  hukumÃƒâ€šÃ‚Â  yangÃƒâ€šÃ‚Â  sangatÃƒâ€šÃ‚Â  kuatÃƒâ€šÃ‚Â  mengenaiÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  perlindunganÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  terhadapÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  masyarakatÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  untukÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  terhindarÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  dariÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  kualitasÃƒâ€šÃ‚Â Ãƒâ€šÃ‚Â  lingkungan yang tidak baik dan termasuk sengketa lingkungan hidup. Akan tetapi dalam pelaksanaanya penegakan lingkungan hidup masih terkendala oleh beberapa faktor maka dari itu perlu sosialisasi yang masif serta di buatkan aturan pelaksanaan sebagai penunjang UUPLH agar perlindungan terhadap masarakat terhadap pencemaran lingkungan dapat terwujut.Ãƒâ€šÃ‚Â Kata Kunci: Perlindungan masyarakat, Lingkungan Hidup.Ãƒâ€šÃ‚Â The right to a good and healthy environment as regulated in Article 28 (h) of the Constitution of the Republic of Indonesia (UUD 1945) has legal implications so that the state always provides environmental quality in accordance with the basic norms of the 1945 Constitution. Even in Article 33 of the 1945 Constitution it is mandated that "the earth, water and natural resources contained therein are controlled by the state and used for the greatest prosperity of the people". In order to realize the protection of the environment, the government issued various legal policies related to environmental issues and one of the most important legal products is Law Number 32 of 2009 concerning Environmental Protection and Management. The UUPPLH has provided a very strong legal basis regarding the protection of the community to avoid bad environmental quality and includes environmental disputes. However, the implementation of environmental enforcement is still constrained by several factors, therefore a massive socialization is needed and rules of implementation are made to support the UUPLH so that the protection of the community against environmental pollution can be threatened.Ãƒâ€šÃ‚Â Keywords: Community Protection, Environment.